Petrochemical into Environment and Health Effects† - Kataria, H.C.; Iqbal, S.A. (Asian Journal of Chemistry, 2010)
Petroleum damages the environment due to its physical nature. Formation of petroleum, organic components of petroleum, chemical effect of oil (causes anaesthesia and narcosis and low b.p. aromatic hydrocarbons are toxic), and other polycyclic aromatic hydrocarbons are discussed in this study. Route of metabolism of aromatic compounds is the formation of areneoxides ingested in mammals including changes in the P-450 cystochrome enzymes (cited mainly in liver, but also in kindeys, lungs and intestines).